Cytochrome P450 monooxygenase analysis in free-living and symbiotic microalgae Coccomyxa sp. C-169 and Chlorella sp. NC64A - Mthakathi, Ntsane Trevor; Kgosiemang, Ipeleng Kopano Rosinah; Chen, Wanping; Mohlatsane, Molikeng Eric; Mojahi, Thebeyapelo Jacob; Yu, Jae-Hyuk; Mashele, Samson Sitheni; Syed, Khajamohiddin (Algae, 2015)
Microalgae research is gaining momentum because of their potential biotechnological applications, including the generation of biofuels. Genome sequencing analysis of two model microalgal species, polar free-living Coccomyxa sp. C-169 and symbiotic Chlorella sp. NC64A, revealed insights into the factors responsible for their lifestyle and unravelled biotechnologically valuable proteins. However, genome sequence analysis under-explored cytochrome P450 monooxygenases (P450s), heme-thiolate proteins ubiquitously present in species belonging to different biological kingdoms. In this study we performed genome data-mining, annotation and comparative analysis of P450s in these two model algal species. Sixty-nine P450s were found in two algal species. Coccomyxa sp. showed 40 P450s and Chlorella sp. showed 29 P450s in their genome. Sixty-eight P450s (>100 amino acid in length) were grouped into 32 P450 families and 46 P450 subfamilies. Among the P450 families, 27 P450 families were novel and not found in other biological kingdoms. The new P450 families are CYP745-CYP747, CYP845-CYP863, and CYP904-CYP908. Five P450 families, CYP51, CYP97, CYP710, CYP745, and CYP746, were commonly found between two algal species and 16 and 11 P450 families were unique to Coccomyxa sp. and Chlorella sp. Synteny analysis and gene-structure analysis revealed P450 duplications in both species. Functional analysis based on homolog P450s suggested that CYP51 and CYP710 family members are involved in membrane ergosterol biosynthesis. CYP55 and CYP97 family members are involved in nitric oxide reduction and biosynthesis of carotenoids. This is the first report on comparative analysis of P450s in the microalgal species Coccomyxa sp. C-169 and Chlorella sp. NC64A.
Published Article
Keywords: carotenoid biosynthesis; Chlorella sp; NC64A; Coccomyxa sp. C-169; cytochrome P450 monooxygenases; nitric oxide reductase; P450nor; symbiosis